Spatial and Temporal Changes in Salinity of Arable Lands in Shah Bandar Tehsil, Thatta District, Sindh - Shella Bano; Viqar Husain; Ghulam Murtaza; Salman Zubair; Syed Waseem Haider (International Journal of Economic and Environmental Geology, 2016)
The cultivable lands are reducing significantly in hot and dry arid regions of the world due to soil salinity and sodicity resulting in yield losses. Similarly, the coastal Shah Bandar Tehsil of Thatta district is also severely affected by different levels of soil salinity and sodicity. The topography of the area is uneven, so ill drained depressions and saline creeks are common. This area was worst affected by floods of 2010 and 2011. The flood water kept standing for several months causing water logging in the area. Irrigation is done with perennial and non perennial canals, as groundwater is highly saline due to saltwater flooding and seawater intrusion. In order to identify spatial and temporal variations in soil salinity and sodicity, 48 soil samples were collected from six sites of Shah Bandar Tehsil during Post and Pre monsoon seasons of 2011-2013. Physicochemical data indicate that average pHe of soil ranges between 7.4 and 7.8 during Post and Pre monsoon seasons of 2011-2013. While soil salinity (ECe) and sodicity (SAR) ranged from 1.09 to 47.10 dS/m and 2.43 to 43.79 during Post monsoon seasons of 2011 and 2013 respectively. Whereas, during Premonsoon seasons of 2012 and 2013, EC and SAR ranged from 2.30 to 65.8 dS/m and 3.12 to 50.51 respectively. Thus, soil salinity and sodicity vary from site to site and season to season due to arid climate, high evapotranspiration and fallow lands because of reduced flow of freshwater and seawater intrusion. Data show that the soil quality improved significantly as indicated by reduced soil salinity and sodicity due to floods of 2010 and 2011. Keywords: Soil salinity, temporal and spatial variation, coastal area, seawater intrusion, flood effects.